PENINGKATAN MONITORING KUALITAS AIR KOLAM BUDIDAYA IKAN DAN PENGEMBANGAN PEMASARAN PRODUK OLAHAN IKAN KELOMPOK KUMIS LELE KELURAHAN PANJANG JIWO, KOTA SURABAYA - Lestariningsih, Diana; Wellyantony , Antonius Jan; Gunadhi, Albert (Universitas Mataram, 2025)
The Kumis Lele Group, located in Panjang Jiwo, Surabaya, produces a variety of processed fish products such as shredded fish, fish skin products, fish balls, seasoned catfish, nuggets, risoles, dumplings, spring rolls, and stuffed tofu. Despite this potential, the group faces two major challenges: (1) the inability to produce fish seeds continuously due to high mortality rates, and (2) inconsistent sales of processed fish products, which are either sold quickly or remain unsold for extended periods. This community service program aimed to (1) implement a water quality monitoring device measuring Potential of Hydrogen (pH) and Dissolved Oxygen (DO), with real-time data transmission to the partner leader’s mobile phone via the Telegram application, and (2) improve marketing development through enhanced product photography and training on branding, selling techniques, and marketing strategies. The activities included socialization of the program plan, training in photography, dissemination of marketing strategies, and training on the use of the pH and DO monitoring device. The results showed that the device functioned effectively, transmitting accurate data and improving fish seed survival, with production reaching 50,000 seeds within three months. In terms of marketing, nine high-quality product photos were produced and printed as stickers for both offline and digital promotion. Furthermore, participants’ knowledge of branding, selling techniques, and marketing strategies improved significantly, with average scores increasing from 38% to 82%, demonstrating the effectiveness of the program. In conclusion, this program successfully enhanced aquaculture productivity and strengthened the marketing capacity of the Kumis Lele Group